The role of renewable energy in Nigeria’s energy transformation (2020)
The domination of the energy mix of most countries across the globe by fossil fuel has been having serious effects on the climatic conditions, resulting from constant emission of greenhouse gases, GHG. It has also been found to be detrimental to human health, and as such, not less than 5 million cases of premature deaths due to local air pollution are annually recorded. Therefore, to combat GHG emissions and air pollution, there is an urgent need to adopt clean sources of energy generation, such as the renewables. This chapter discusses the meaning, history and benefits of renewable energy, highlights the common forms and sources, dwells on energy trends in Nigeria, reflects on hydropower plants in relation to technology, material selection and efficiency, as well as draws conclusions from areas covered.